DIFFICULTIES IN PERCEIVING AND COMPREHENDING A CULTURALLY EMBEDDED FOREIGN TEXT - Aminova G.R. (ZAMONAVIY TILSHUNOSLIK ISTIQBOLLARI: MUAMMOLAR VA YUTUQLAR MAVZUSIDA XALQARO ILMIY AMALIY ANJUMAN, 2025)
This article explores the peculiarities in perceiving and comprehending foreign linguocultural texts, focusing on the comparative analysis of Russian, English, and Uzbek. It examines how these languages reflect unique ethnocultural models and communicative frameworks, highlighting cognitive and cultural challenges in text interpretation. Drawing on frame semantics and reflective understanding, the study shows that comprehension involves not only linguistic competence but also culturally embedded conceptual structures and interpretive strategies. The research emphasizes that while linguistic systems differ significantly, reflective reality allows individuals to overcome barriers and access deeper meanings within foreign texts.